Collectively coincidence-type results and applications. Issue 3 (11th February 2023) - O'Regan, Donal
Abstract : Based on the well-known Brouwder fixed-point theorem in this paper we will present a variety of collectively coincidence-type results for general classes of maps. Our theory will automatically generate analytic alternatives and minimax inequalities.